2015
DOI: 10.1166/jnn.2015.9717
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Adenine and Guanine Using Cadmium Selenide Quantum Dots-Graphene Oxide Nanocomposite Modified Electrode

Abstract: A novel electrochemical sensor was fabricated by immobilizing Cadmium Selenide Quantum Dots (CdSe QDs)-Graphene Oxide (GO) nanocomposite on a paraffin wax impregnated graphite electrode (PIGE) and was used for the simultaneous determination of adenine and guanine. The CdSe QDs-GO nanocomposite was prepared by ultrasonication and was characterized with spectroscopic and microscopic techniques. The nanocomposite modified electrode was characterized by cyclic voltammetry (CV). The modified electrode showed excell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Figure shows the quantitative calibration plot (in presence of different concentration values of G, performed by DPV and the corresponding quantitative parameters are reported on Table . FB‐SPE shows the widest range of linearity for the analytical responses to the concentration of G; a good sensitivity (lower than that exhibited by the as reported Graphitized Mesoporous Carbon (GMC) modified GCE, probably for the highest surface nominal area exhibited by the GMC electrodic materials) and the lowest detection limit, if compared with other electrochemical devices reported in literature , and summarized in Table . Also the FB‐SPE show the best intra‐ and inter‐electrodes reproducibility, and the fastest response time (useful to carry out a real time analysis of a large number of samples during the same day, applying disposable, miniaturized and partially automated electrochemical sensors, modified with functionalized fullerenes).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows the quantitative calibration plot (in presence of different concentration values of G, performed by DPV and the corresponding quantitative parameters are reported on Table . FB‐SPE shows the widest range of linearity for the analytical responses to the concentration of G; a good sensitivity (lower than that exhibited by the as reported Graphitized Mesoporous Carbon (GMC) modified GCE, probably for the highest surface nominal area exhibited by the GMC electrodic materials) and the lowest detection limit, if compared with other electrochemical devices reported in literature , and summarized in Table . Also the FB‐SPE show the best intra‐ and inter‐electrodes reproducibility, and the fastest response time (useful to carry out a real time analysis of a large number of samples during the same day, applying disposable, miniaturized and partially automated electrochemical sensors, modified with functionalized fullerenes).…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose is more important to consider the current density (A/cm 2 ) rather than the only I/A parameter. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 [37][38][39][40][41][42][43], and summarized in Table 3. Also the FB-SPE show the best intra-and inter-electrodes reproducibility, and the fastest response time (useful to carry out a real time analysis of a large number of samples during the same day, applying disposable, miniaturized and partially automated electrochemical sensors, modified with functionalized fullerenes).…”
Section: Linear Regression Equationmentioning
confidence: 99%
“…The combination of graphene and metal selenides can fabricated the composites with enhanced the electron transfer property, improved surface area and increased density of the electrocatalytically active sites, compared with the pure graphene or selenides [144]. For example, CdSe, SnSe 2 , MoSe 2 , CuSe, Ag 2 Se functionalized graphene biosensor have achieved the electrochemical detection of Adenine, Guanine, carbendazim, dopamine, eugenol and serotonin with high sensitivity and selectivity [144a, b, 145]. Furthermore, researchers found that the selenides with bimetallic active sites have better selectivity and catalytic activity than single metal catalysts [146].…”
Section: Fabrication Of Graphene‐based Biosensorsmentioning
confidence: 99%
“…The modified electrode showed excellent electrocatalytic activity for the oxidative determination of adenine and guanine with a good peak separation of 0.31 V. The detection limits of adenine and guanine were 0.028 and 0.055 µM, respectively. The method was employed for herring sperm DNA as an example of a real sample [ 132 ].…”
Section: Biomedical Applicationsmentioning
confidence: 99%